Ecological Responsible throughout Infrastructure Project Life Cycle - Ismail, Sushilawati (Penerbit UTHM, 2020)
United Nations’ leaders pledged to protect the planet through sustainable utilization of natural resources and work on climate change issues. Apart from that, the concern is about the ecological responsibility of the construction industry towards promoting sustainable development. This underlies the need to explore how and what are the environmental consequences of a construction project, particularly on infrastructure development. Being the largest contributor to the energy and waste generation, there is a growing realization of the irreversible impact of non-replaceable natural resources, which could lead to complete depletion. This paper describes specific ecological concern such as resources utilization and energy consumption throughout the lifecycle of an infrastructure project. Feasible mechanisms and practices that could improve the environmental performance also presented to promote sustainability in infrastructure project development in every project phase. The literature study shows that kind of approaches carries with them various limitations depending on the type of infrastructure. The innovation of new materials, designs, construction methods or techniques for infrastructure in optimizing resource consumption, environmental impact, and waste production need to be developed and assessed over their life cycle. In turn, this will promote a robustly built environment as a result of more sustainable infrastructure, better conservation, and efficient space utilization.